THE PREMISES AND MAIN ASPECTS OF CREATION OF A SUBSYSTEM OF GEOLOGIC ENVIRONMENT ANALYSIS FOR GEOGRAPHIC INFORMATION SYSTEMS FOR TRANS-CONTINENTAL PIPELINES - IVANIK, O.; MYKHAILENKO, A.; SHEVCHUK, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2004)
Problems of the creation of a subsystem for a geologic environment analysis for Geographic information systems of trans-continental pipelines have been discussed. It is demonstrated that methodical basis of geological conditions assessment is the complex integral assessment of geologic environment conditions with the creation and analysis of analytical blocks. Method of creation and actualization of cartographical models depicting the geologic environment and its variation in space and in time should become a main method of a subsystem of geologic environment analysis GIS TP.